MENINGKATKAN PEMAHAMAN OPERASI HITUNG PENGURANGAN DAN PENJUMLAHAN BILANGAN BULAT DENGAN MEDIA MUZAX - Ketaren, Maya Alemina; Rarastika, Nur; Endang, Sri; Khairani, Devi; Mailani, Elvi (JGK (Jurnal Guru Kita), 2019)
Abstract: Improve Understanding of Operations in Calculating Subtraction and Adding Round Numbers with Muzax Media. The low learning outcomes of class VI SDN 104223 Bingkawan in addition and reduction of integer material indicate that students’ understanding of the material is still low, one of the reasons is the absence of learning media for the material. The purpose of the mentoring and training activities is to improve students’ understanding of the sum and counting operations of integers. This activity was conducted on April 9, 2019 until May 25, 2019 at 104223 Bingkawan SDN with pre-test and post-test techniques. After carrying out mentoring activities using MUZAX (Multifunctional Zahlen Box) media on addition learning and integer reduction for 24 students of class VI, there was an increase in learning outcomes by 75%. Keywords: Sum Numbers Addition and Reduction, MUZAX, Primary School Students. Abstrak: Meningkatkan Pemahaman Operasi Hitung Pengurangan dan Penjumlahan Bilangan Bulat Dengan Media Muzax. Rendahnya hasil belajar siswa kelas VI SDN 104223 Bingkawan pada materi penjumlahan dan pengurangan bilangan bulat menunjukkan bahwa pemahaman siswa pada materi tersebut masih rendah, salah satu penyebabnya adalah tidak adanya media pembelajaran untuk materi tersebut. Tujuan dari dari kegiatan pendampingan dan pelatihan ini adalah untuk meningkatkan pemahaman siswa menganai operasi hitung penjumlahan dan pengurangan bilangan bulat.Kegiatan ini dilakukan pada 8 April 2019 sampai 25 Mei 2019 di SDN 104223 Bingkawan dengan teknik pre-test dan post-test. Setelah dilaksanakan kegiatan pendampingan dengan menggunakan media MUZAX (Multifnctional Zahlen Box) pada pembelajaran penjumlahan dan pengurangan bilangan bulat terhadap 24 siswa kelas VI, terjadi peningkatan hasil belajar sebesar 75% . Kata Kunci : Penjumlahan dan Pengurangan Bilangan Bulat, MUZAX, Siswa Sekolah Dasar.